Bidirectionally Regulating Gamma Oscillations in Wilson-Cowan Model by Self-Feedback Loops: A Computational Study - Li, XiuPing; Li, ZhengHong; Yang, WanMei; Wu, Zhen; Wang, JunSong (Frontiers in Systems Neuroscience, 2022)
Wilson-Cowan model can emulate gamma oscillations, thus is extensively used to research the generation of gamma oscillations closely related to cognitive functions. Previous studies have revealed that gamma oscillations of the model can be modulated by excitatory and inhibitory inputs to the model, sigmoid functions and time constants of excitatory and inhibitory populations, respectively. Inhibitory and excitatory self-feedback loops are important structural features of the model, however, its functional role in the regulation of gamma oscillations of the model is still unclear. In the present study, bifurcation analysis and spectrum analysis are employed to elucidate the regulating mechanism of gamma oscillations underlined by the inhibitory and excitatory self-feedback loops, especially how the two self-feedback loops cooperate to generate the gamma oscillations and regulate the oscillation frequency. The results show that, on one hand, the inhibitory self-feedback loop is not conducive to the generation of gamma oscillations, and increased inhibitory self-feedback strength facilitates the enhancement of the oscillation frequency. On the other hand, the excitatory self-feedback loop promotes the generation of gamma oscillations, and increased excitatory self-feedback strength leads to the decrease of oscillation frequency. To sum up, Inhibitory and excitatory self-feedback loops play a complementary role in generating and regulating the gamma oscillation in Wilson-Cowan model, and cooperate to bidirectionally regulate the gamma-oscillation frequency in a more flexible manner. These results might provide testable hypotheses for future experimental researches.